Female Body’s in Advertisements: A Foucauldian Analysis - Paudel, Jay Ram (Chaturbhujeshwar Academic Journal, 2023)
This research study examines the articulation of the female body in advertisements through the intersecting lenses of Foucauldian perspectives. In the context of contemporary consumer culture where advertisements play a pivotal role in shaping social perceptions of gender and beauty, this research seeks to unravel the complex web of power, discourse, and commodification regarding the portrayal of women's bodies. The analysis delves into how capitalism commodifies the female body, turning it into a product to circulate in the market. The study investigates the economic relations and labor conditions involved in the production of these images, shedding light on the exploitative mechanisms within the advertising industry. It also explores how consumerism and the pursuit of profit contribute to the perpetuation of idealized beauty standards. Simultaneously, drawing from Foucault's theories, the research investigates the ways in which power operates within the discourse of advertisements. It uncovers how advertising normalizes specific beauty ideals, imposes disciplinary domains regimes, and invites viewers to engage in a surveillance-based gaze that judges and categorizes female bodies. This study revealed that advertisements commodify the female body, reducing women to objects that can be bought and sold, perpetuating unrealistic beauty standards and creating a culture where women feel alienated from their own bodies, all driven by the profit motive of corporations and reinforcing the capitalist notion that everything, including beauty, has a price. By elucidating these dynamics, the research contributes to a critical discourse on the role of advertising in reinforcing or challenging gender norms and the broader socio-economic system.